Uncertainty Quantification of Finite Element Strain Predictions for a Nitinol Medical Device: Influence of Input Parameter Probability Distribution on Output Uncertainty - Ian A. Carr; Kenneth I. Aycock; Harshad Paranjape; Craig Bonsignore; Jason D. Weaver; Brent A. Craven (Cardiovascular Engineering and Technology, 2026)

Early root architectural traits and their relationship with yield in Ipomoea batatas L - Luis O. Duque; Gabriella Hoffmann; Kenneth V. Pecota; G. Craig Yencho (Plant and Soil, 2025)

The effect of enhanced glycolysis on cardiac aging - Anna Faakye; Kylene M. Harold; Satoshi Matsuzaki; Atul Pranay; Maria F. Mendez Garcia; Brooke L. Loveland; Sandra N. Rigsby; Frederick F. Peelor; Craig Eyster; Benjamin F. Miller; Timothy M. Griffin; Michael Kinter; et al. (GeroScience, 2025)
Cardiac aging is associated with metabolic changes, including an increased reliance on glycolysis, and an increased susceptibility to cardiovascular diseases. This study explores the relationship between enhanced cardiac glycolysis and aging using the Glyco Hi mouse model, characterized by constitutively elevated glycolysis. We compared cardiac function, metabolism, mitochondrial performance, and hallmarks of aging between aged (21 and 24 months) Glyco Hi and wild-type (WT) mice across sexes. Our findings reveal modest reductions in cardiac function in aged Glyco Hi mice compared to WT mice, with sex-specific differences in heart size and collagen concentration. Female Glyco Hi hearts exhibited hypertrophy without fibrosis, while males showed elevated collagen levels. Whole-body metabolic assessments revealed similar energy expenditure and respiratory patterns across genotypes, with females displaying less circadian-associated variation in metabolism. Mitochondrial analyses showed that aged Glyco Hi hearts maintained metabolic adaptations favoring glycolysis but did not exhibit significant bioenergetic dysfunction or oxidative stress. Pyruvate dehydrogenase activity, initially elevated in younger Glyco Hi hearts, normalized to WT levels with age. Proteomic and metabolomic analyses highlighted distinct profiles between genotypes, with Glyco Hi hearts exhibiting increased glycolytic enzyme levels and reduced abundance of fatty acid oxidation proteins. Despite these differences, indicators of oxidative stress, proteostasis, and cellular senescence were comparable between genotypes, suggesting no acceleration of aging-related dysfunction. This study demonstrates that increased cardiac glycolysis alone does not suffice to drive accelerated cardiac aging. Instead, metabolic and functional changes in aged Glyco Hi hearts reflect adaptations rather than pathological declines, providing insights into potential metabolic targets for interventions against cardiac aging.

Predicting sweetpotato traits using machine learning: Impact of environmental and agronomic factors on shape and size - Hangjin Liu; Shelly Hunt; G. Craig Yencho; Kenneth V. Pecota; Russell Mierop; Cranos M. Williams; Daniela S. Jones (Computers and Electronics in Agriculture, 2024)

Corrigendum: Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2024)

Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2023)
We contend that ocean turbulent fluxes should be included in the list of Essential Ocean Variables (EOVs) created by the Global Ocean Observing System. This list aims to identify variables that are essential to observe to inform policy and maintain a healthy and resilient ocean. Diapycnal turbulent fluxes quantify the rates of exchange of tracers (such as temperature, salinity, density or nutrients, all of which are already EOVs) across a density layer. Measuring them is necessary to close the tracer concentration budgets of these quantities. Measuring turbulent fluxes of buoyancy ( J b ), heat ( J q ), salinity ( J S ) or any other tracer requires either synchronous microscale (a few centimeters) measurements of both the vector velocity and the scalar (e.g., temperature) to produce time series of the highly correlated perturbations of the two variables, or microscale measurements of turbulent dissipation rates of kinetic energy ( ϵ ) and of thermal/salinity/tracer variance ( χ ), from which fluxes can be derived. Unlike isopycnal turbulent fluxes, which are dominated by the mesoscale (tens of kilometers), microscale diapycnal fluxes cannot be derived as the product of existing EOVs, but rather require observations at the appropriate scales. The instrumentation, standardization of measurement practices, and data coordination of turbulence observations have advanced greatly in the past decade and are becoming increasingly robust. With more routine measurements, we can begin to unravel the relationships between physical mixing processes and ecosystem health. In addition to laying out the scientific relevance of the turbulent diapycnal fluxes, this review also compiles the current developments steering the community toward such routine measurements, strengthening the case for registering the turbulent diapycnal fluxes as an pilot Essential Ocean Variable.

Features of turbulence during wildland fires in forested and grassland environments - Ajinkya Desai; Warren E. Heilman; Nicholas S. Skowronski; Kenneth L. Clark; Michael R. Gallagher; Craig B. Clements; Tirtha Banerjee (Agricultural and Forest Meteorology, 2023)

Searching for Oxygen: Dynamic Movement Responses of Juvenile Spot (Leiostomus xanthurus) in an Intermittently Hypoxic Estuary - J. Kevin Craig; Klaus B. Huebert; Kenneth A. Rose; James A. Rice; Damian C. Brady (Estuaries and Coasts, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

A phenomic modeling approach for using chlorophyll-a fluorescence-based measurements on coral photosymbionts - Kenneth D. Hoadley; Grant Lockridge; Audrey McQuagge; K. Blue Pahl; Sean Lowry; Sophie Wong; Zachary Craig; Chelsea Petrik; Courtney Klepac; Erinn M. Muller (Frontiers in Marine Science, 2023)
We test a newly developed instrument prototype which utilizes time-resolved chlorophyll- a fluorescence techniques and fluctuating light to characterize Symbiodiniaceae functional traits across seven different coral species under cultivation as part of ongoing restoration efforts in the Florida Keys. While traditional chlorophyll- a fluorescence techniques only provide a handful of algal biometrics, the system and protocol we have developed generates > 1000 dynamic measurements in a short (~11 min) time frame. Resulting ‘high-content’ algal biometric data revealed distinct phenotypes, which broadly corresponded to genus-level Symbiodiniaceae designations determined using quantitative PCR. Next, algal biometric data from Acropora cervicornis (10 genotypes) and A. palmata (5 genotypes) coral fragments was correlated with bleaching response metrics collected after a two month-long exposure to high temperature. A network analysis identified 1973 correlations (Spearman R > 0.5) between algal biometrics and various bleaching response metrics. These identified biomarkers of thermal stress were then utilized to train a predictive model, and when tested against the same A. cervicornis and A. palmata coral fragments, yielded high correlation (R = 0.92) with measured thermal response (reductions in absorbance by chlorophyll-a). When applied to all seven coral species, the model ranked fragments dominated by Cladocopium or Breviolum symbionts as more bleaching susceptible than corals harboring thermally tolerant symbionts ( Durusdinium ). While direct testing of bleaching predictions on novel genotypes is still needed, our device and modeling pipeline may help broaden the scalability of existing approaches for determining thermal tolerance in reef corals. Our instrument prototype and analytical pipeline aligns with recent coral restoration assessments that call for the development of novel tools for improving scalability of coral restoration programs.

T-cell cellular stress and reticulocyte signatures, but not loss of naïve T lymphocytes, characterize severe COVID-19 in older adults - Mladen Jergović; Makiko Watanabe; Ruchika Bhat; Christopher P. Coplen; Sandip A. Sonar; Rachel Wong; Yvonne Castaneda; Lisa Davidson; Mrinalini Kala; Rachel C. Wilson; Homer L. Twigg; Kenneth Knox; et al. (GeroScience, 2023)

Empirical nitrogen and sulfur critical loads of U.S. tree species and their uncertainties with machine learning - Nathan R. Pavlovic; Shih Ying Chang; Jiaoyan Huang; Kenneth Craig; Christopher Clark; Kevin Horn; Charles T. Driscoll (Science of The Total Environment, 2023)

Seasonality of dissolved organic matter in lagoon ecosystems along the Alaska Beaufort Sea coast - Craig T. Connolly; Byron C. Crump; Kenneth H. Dunton; James W. McClelland (Limnology and Oceanography, 2021)
Seasonal variations in dissolved organic matter (DOM) fluxes from land to sea have been well documented in the Arctic, yet remarkably little is known about how DOM varies seasonally within Arctic coastal waters. This is particularly true for shallow inshore environments. Here we document seasonality of DOM in lagoons along the eastern Alaska Beaufort Sea coast during the spring ice break‐up (June), summer open‐water (August), and late winter ice‐covered (April) periods. We measured dissolved organic carbon (DOC) concentrations, C:N ratios, and chromophoric DOM (CDOM) characteristics (SUVA 254 and S 275–295 ). On average, lagoon DOC was highest during spring (~200 μ M) and lowest during winter (~120 μ M). C:N and SUVA 254 also differed markedly between spring (C:N ~ 28; SUVA 254 ~ 3.5 L mg C −1 m −1 ) and winter (C:N ~ 16; SUVA 254 ~ 2.2 L mg C −1 m −1 ). Average S 275–295 values (~14–17 × 10 −3 nm −1 ) were not significantly different among seasons, but variability in S 275–295 was much lower in spring. This was attributed to terrestrial runoff based on its relatively uniform composition during the spring freshet. Seasonal variations in lagoon DOM were broadly correlated with variations in salinity (i.e., lagoon water transitioned from largely fresh in spring to hypersaline in winter), but a mixing analysis revealed strong evidence of processing and net DOC generation in summer. We also found evidence of DOC processing and build‐up under the ice over the winter. This baseline understanding of DOM seasonality in Arctic lagoons is essential for evaluating climate‐linked impacts on Arctic coastal ecosystems and broader feedbacks associated with carbon cycling.

Discovery of a major QTL for root-knot nematode (Meloidogyne incognita) resistance in cultivated sweetpotato (Ipomoea batatas) - Bonny Michael Oloka; Guilherme da Silva Pereira; Victor A. Amankwaah; Marcelo Mollinari; Kenneth V. Pecota; Benard Yada; Bode A. Olukolu; Zhao-Bang Zeng; G. Craig Yencho (Theoretical and Applied Genetics, 2021)
Key message Utilizing a high-density integrated genetic linkage map of hexaploid sweetpotato, we discovered a major dominant QTL for root-knot nematode (RKN) resistance and modeled its effects. This discovery is useful for development of a modern sweetpotato breeding program that utilizes marker-assisted selection and genomic selection approaches for faster genetic gain of RKN resistance. Abstract The root-knot nematode [Meloidogyne incognita (Kofoid & White) Chitwood] (RKN) causes significant storage root quality reduction and yields losses in cultivated sweetpotato [Ipomoea batatas (L.) Lam.]. In this study, resistance to RKN was examined in a mapping population consisting of 244 progenies derived from a cross (TB) between ‘Tanzania,’ a predominant African landrace cultivar with resistance to RKN, and ‘Beauregard,’ an RKN susceptible major cultivar in the USA. We performed quantitative trait loci (QTL) analysis using a random-effect QTL mapping model on the TB genetic map. An RKN bioassay incorporating potted cuttings of each genotype was conducted in the greenhouse and replicated five times over a period of 10 weeks. For each replication, each genotype was inoculated with ca. 20,000 RKN eggs, and root-knot galls were counted ~62 days after inoculation. Resistance to RKN in the progeny was highly skewed toward the resistant parent, exhibiting medium to high levels of resistance. We identified one major QTL on linkage group 7, dominant in nature, which explained 58.3% of the phenotypic variation in RKN counts. This work represents a significant step forward in our understanding of the genetic architecture of RKN resistance and sets the stage for future utilization of genomics-assisted breeding in sweetpotato breeding programs.

Biomass Production of Prairie Cordgrass (Spartina pectinata Link.) Using Urea and Kura Clover (Trifolium ambiguum Bieb.) as a Source of Nitrogen - SungUn Kim; Kenneth Albrecht; Craig Sheaffer; Dokyoung Lee; Senthil Subramanian; Vance Owens (BioEnergy Research, 2020)
Optimizing nitrogen (N) management is an important factor for sustainable perennial biomass systems. However, N application is costly, both financially and environmentally. Our objectives were to determine: (1) N rate and plant spacing effects on yield and yield components of prairie cordgrass swards and (2) fertilizer N replacement value (FNRV) of kura clover in prairie cordgrass-kura clover binary mixtures. Plots were established in Illinois, Minnesota, South Dakota, and Wisconsin, USA, in 2010. Kura clover was transplanted on 30-cm centers in all treatments in which it was a component; prairie cordgrass seedlings were transplanted within the kura clover on 60- and 90-cm centers. Monoculture prairie cordgrass stands were established at the same population densities of mixed stands and fertilized with 0, 75, 150, or 225 kg N ha -1 . Biomass was harvested in the autumn from 2011 to 2013. N (urea), year, plant spacing, and year × plant spacing affected prairie cordgrass production at all locations. Prairie cordgrass yield increased with N application, but the response varied by location. N application tended to increase prairie cordgrass tiller density and consistently increased tiller mass. Prairie cordgrass yield with 0 N was equal to or less than the yield of prairie cordgrass/kura clover mixtures at all locations in 2011 and 2012; however, kura clover provided a FNRV of 25–82 kg N ha -1 to prairie cordgrass in 2013. Kura clover has potential to provide N to prairie cordgrass in binary mixtures of these two species and on land that may not be easily farmed due to wetness.

A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Henry C. Bittig; Tanya L. Maurer; Joshua N. Plant; Catherine Schmechtig; Annie P. S. Wong; Hervé Claustre; Thomas W. Trull; T. V. S. Udaya Bhaskar; Emmanuel Boss; Giorgio Dall’Olmo; Emanuele Organelli; Antoine Poteau; et al. (Frontiers in Marine Science, 2019)

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Aftertreatment Protocols for Catalyst Characterization and Performance Evaluation: Low-Temperature Oxidation, Storage, Three-Way, and NH3-SCR Catalyst Test Protocols - Kenneth G. Rappé; Craig DiMaggio; Josh A. Pihl; Joseph R. Theis; Se H. Oh; Galen B. Fisher; Jim Parks; Vencon G. Easterling; Ming Yang; Mark L. Stewart; Kenneth C. Howden (Emission Control Science and Technology, 2019)

Pentagalloyl Glucose and Its Functional Role in Vascular Health: Biomechanics and Drug-Delivery Characteristics - Sourav S. Patnaik; Dan T. Simionescu; Craig J. Goergen; Kenneth Hoyt; Shashank Sirsi; Ender A. Finol (Annals of Biomedical Engineering, 2019)

Oxygen Optode Sensors: Principle, Characterization, Calibration, and Application in the Ocean - Henry C. Bittig; Arne Körtzinger; Craig Neill; Eikbert van Ooijen; Joshua N. Plant; Johannes Hahn; Kenneth S. Johnson; Bo Yang; Steven R. Emerson (Frontiers in Marine Science, 2018)

Modeling the Population Effects of Hypoxia on Atlantic Croaker (Micropogonias undulatus) in the Northwestern Gulf of Mexico: Part 2—Realistic Hypoxia and Eutrophication - Kenneth A. Rose; Sean Creekmore; Dubravko Justić; Peter Thomas; J. Kevin Craig; Rachael Miller Neilan; Lixia Wang; Md Saydur Rahman; David Kidwell (Estuaries and Coasts, 2018)

Modeling the Population Effects of Hypoxia on Atlantic Croaker (Micropogonias undulatus) in the Northwestern Gulf of Mexico: Part 1—Model Description and Idealized Hypoxia - Kenneth A. Rose; Sean Creekmore; Peter Thomas; J. Kevin Craig; Md Saydur Rahman; Rachael Miller Neilan (Estuaries and Coasts, 2018)

Evaluating Tidal Wetland Restoration Performance Using National Estuarine Research Reserve System Reference Sites and the Restoration Performance Index (RPI) - Kenneth B. Raposa; Scott Lerberg; Craig Cornu; John Fear; Nina Garfield; Christopher Peter; Robin L.J. Weber; Gregg Moore; David Burdick; Michelle Dionne (Estuaries and Coasts, 2018)

Age‐specific vibrissae growth rates: A tool for determining the timing of ecologically important events in Steller sea lions - Lorrie D. Rea; Aaron M. Christ; Alison B. Hayden; Vicki K. Stegall; Sean D. Farley; Craig A. Stricker; Jo‐Ann E. Mellish; John M. Maniscalco; Jason N. Waite; Vladimir N. Burkanov; Kenneth W. Pitcher (Marine Mammal Science, 2015)
Steller sea lions ( SSL ; Eumetopias jubatus ) grow their vibrissae continually, providing a multiyear record suitable for ecological and physiological studies based on stable isotopes. An accurate age‐specific vibrissae growth rate is essential for registering a chronology along the length of the record, and for interpreting the timing of ecologically important events. We utilized four methods to estimate the growth rate of vibrissae in fetal, rookery pup, young‐of‐the‐year ( YOY ), yearling, subadult, and adult SSL . The majority of vibrissae were collected from SSL live‐captured in Alaska and Russia between 2000 and 2013 ( n = 1,115), however, vibrissae were also collected from six adult SSL found dead on haul‐outs and rookeries during field excursions to increase the sample size of this underrepresented age group. Growth rates of vibrissae were generally slower in adult (0.44 ± 0.15 cm/mo) and subadult (0.61 ± 0.10 cm/mo) SSL than in YOY (0.87 ± 0.28 cm/mo) and fetal (0.73 ± 0.05 cm/mo) animals, but there was high individual variability in these growth rates within each age group. Some variability in vibrissae growth rates was attributed to the somatic growth rate of YOY sea lions between capture events ( P = 0.014, r 2 = 0.206, n = 29).

Polygonal tundra geomorphological change in response to warming alters future CO 2 and CH 4 flux on the Barrow Peninsula - Mark J. Lara; A. David McGuire; Eugenie S. Euskirchen; Craig E. Tweedie; Kenneth M. Hinkel; Alexei N. Skurikhin; Vladimir E. Romanovsky; Guido Grosse; W. Robert Bolton; Helene Genet (Global Change Biology, 2015)
The landscape of the Barrow Peninsula in northern Alaska is thought to have formed over centuries to millennia, and is now dominated by ice‐wedge polygonal tundra that spans drained thaw‐lake basins and interstitial tundra. In nearby tundra regions, studies have identified a rapid increase in thermokarst formation (i.e., pits) over recent decades in response to climate warming, facilitating changes in polygonal tundra geomorphology. We assessed the future impact of 100 years of tundra geomorphic change on peak growing season carbon exchange in response to: (i) landscape succession associated with the thaw‐lake cycle; and (ii) low, moderate, and extreme scenarios of thermokarst pit formation (10%, 30%, and 50%) reported for Alaskan arctic tundra sites. We developed a 30 × 30 m resolution tundra geomorphology map (overall accuracy:75%; Kappa:0.69) for our ~1800 km² study area composed of ten classes; drained slope, high center polygon, flat‐center polygon, low center polygon, coalescent low center polygon, polygon trough, meadow, ponds, rivers, and lakes, to determine their spatial distribution across the Barrow Peninsula. Land‐atmosphere CO 2 and CH 4 flux data were collected for the summers of 2006–2010 at eighty‐two sites near Barrow, across the mapped classes. The developed geomorphic map was used for the regional assessment of carbon flux. Results indicate (i) at present during peak growing season on the Barrow Peninsula, CO 2 uptake occurs at ‐902.3 10 6 gC‐ CO 2 day −1 (uncertainty using 95% CI is between −438.3 and −1366 10 6 gC‐ CO 2 day −1 ) and CH 4 flux at 28.9 10 6 gC‐ CH 4 day −1 (uncertainty using 95% CI is between 12.9 and 44.9 10 6 gC‐ CH 4 day −1 ), (ii) one century of future landscape change associated with the thaw‐lake cycle only slightly alter CO 2 and CH 4 exchange, while (iii) moderate increases in thermokarst pits would strengthen both CO 2 uptake (−166.9 10 6 gC‐ CO 2 day −1 ) and CH 4 flux (2.8 10 6 gC‐ CH 4 day −1 ) with geomorphic change from low to high center polygons, cumulatively resulting in an estimated negative feedback to warming during peak growing season.

Erratum to: Control of renin gene expression - Sean T. Glenn; Craig A. Jones; Kenneth W. Gross; Li Pan (Pflügers Archiv - European Journal of Physiology, 2013)

Control of rene gene expression - Sean T. Glenn; Craig A. Jones; Kenneth W. Gross; Li Pan (Pflügers Archiv - European Journal of Physiology, 2013)

Comparing volunteer and professionally collected monitoring data from the rocky subtidal reefs of Southern California, USA - David J. Gillett; Daniel J. Pondella; Jan Freiwald; Kenneth C. Schiff; Jennifer E. Caselle; Craig Shuman; Stephen B. Weisberg (Environmental Monitoring and Assessment, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Functional and Genetic Integration in the Skulls of Lake Malawi Cichlids - W. James Cooper; James Wernle; Kenneth Mann; R. Craig Albertson (Evolutionary Biology, 2011)

The Application of the Accelerated Stability Assessment Program (ASAP) to Quality by Design (QbD) for Drug Product Stability - Kenneth Craig Waterman (AAPS PharmSciTech, 2011)

To use or to move: goal-set modulates priming when grasping real tools - Kenneth F. Valyear; Craig S. Chapman; Jason P. Gallivan; Robert S. Mark; Jody C. Culham (Experimental Brain Research, 2011)

Potential for endophyte symbiosis to increase resistance of the native grass Poa alsodes to invasion by the non-native grass Microstegium vimineum - Skylar Craig; Sonia Kannadan; S. Luke Flory; Elizabeth K. Seifert; Kenneth D. Whitney; Jennifer A. Rudgers (Symbiosis, 2011)

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

The Multi-Sensor Improved Sea Surface Temperature (MISST) Project - Chelle Gentemann; Peter Minnett; Joseph Sienkiewicz; Mark DeMaria; James Cummings; Yi Jin; James Doyle; Lew Gramer; Charlie Barron; Kenneth Casey; Craig Donlon (Oceanography, 2009)

Rapid shoot regeneration in industrial ‘high starch’ sweetpotato (Ipomoea batatas L.) genotypes - Monica Santa-Maria; Kenneth V. Pecota; Craig G. Yencho; George Allen; Bryon Sosinski (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Coral Reef Habitats as Surrogates of Species, Ecological Functions, and Ecosystem Services - PETER J. MUMBY; KENNETH BROAD; DANIEL R. BRUMBAUGH; CRAIG, P. DAHLGREN; ALASTAIR R. HARBORNE; ALAN HASTINGS; KATHERINE E. HOLMES; CARRIE V. KAPPEL; FIORENZA MICHELI; JAMES N. SANCHIRICO (Conservation Biology, 2008)
Habitat maps are often the core spatially consistent data set on which marine reserve networks are designed, but their efficacy as surrogates for species richness and applicability to other conservation measures is poorly understood. Combining an analysis of field survey data, literature review, and expert assessment by a multidisciplinary working group, we examined the degree to which Caribbean coastal habitats provide useful planning information on 4 conservation measures: species richness, the ecological functions of fish species, ecosystem processes, and ecosystem services. Approximately one‐quarter to one‐third of benthic invertebrate species and fish species (disaggregated by life phase; hereafter fish species) occurred in a single habitat, and Montastraea ‐dominated forereefs consistently had the highest richness of all species, processes, and services. All 11 habitats were needed to represent all 277 fish species in the seascape, although reducing the conservation target to 95% of species approximately halved the number of habitats required to ensure representation. Species accumulation indices (SAIs) were used to compare the efficacy of surrogates and revealed that fish species were a more appropriate surrogate of benthic species (SAI = 71%) than benthic species were for fishes (SAI = 42%). Species of reef fishes were also distributed more widely across the seascape than invertebrates and therefore their use as a surrogate simultaneously included mangroves, sea grass, and coral reef habitats. Functional classes of fishes served as effective surrogates of fish and benthic species which, given their ease to survey, makes them a particularly useful measure for conservation planning. Ecosystem processes and services exhibited great redundancy among habitats and were ineffective as surrogates of species. Therefore, processes and services in this case were generally unsuitable for a complementarity‐based approach to reserve design. In contrast, the representation of species or functional classes ensured inclusion of all processes and services in the reserve network.

Corrigendum: 2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Hemodynamic and metabolic changes induced by cocaine in anesthetized rat observed with multimodal functional MRI - Karl F. Schmidt; Marcelo Febo; Qiang Shen; Feng Luo; Kenneth M. Sicard; Craig F. Ferris; Elliot A. Stein; Timothy Q. Duong (Psychopharmacology, 2006)

Colonization of nascent, deep‐sea hydrothermal vents by a novel Archaeal and Nanoarchaeal assemblage - Elizabeth A. McCliment; Kenneth M. Voglesonger; Peggy A. O'Day; Eileen E. Dunn; John R. Holloway; S. Craig Cary (Environmental Microbiology, 2006)
Summary Active deep‐sea hydrothermal vents are areas of intense mixing and severe thermal and chemical gradients, fostering a biotope rich in novel hyperthermophilic microorganisms and metabolic pathways. The goal of this study was to identify the earliest archaeal colonizers of nascent hydrothermal chimneys, organisms that may be previously uncharacterized as they are quickly replaced by a more stable climax community. During expeditions in 2001 and 2002 to the hydrothermal vents of the East Pacific Rise (EPR) (9°50′N, 104°17′W), we removed actively venting chimneys and in their place deployed mineral chambers and sampling units that promoted the growth of new, natural hydrothermal chimneys and allowed their collection within hours of formation. These samples were compared with those collected from established hydrothermal chimneys from EPR and Guaymas Basin vent sites. Using molecular and phylogenetic analysis of the 16S rDNA, we show here that at high temperatures, early colonization of a natural chimney is dominated by members of the archaeal genus Ignicoccus and its symbiont, Nanoarchaeum . We have identified 19 unique sequences closely related to the nanoarchaeal group, and five archaeal sequences that group closely with Ignicoccus . These organisms were found to colonize a natural, high temperature protochimney and vent‐like mineral assemblages deployed over high temperature outflows within 92 h. When compared phylogenetically, several of these colonizing organisms form a unique clade independent of those found in mature chimneys and low‐temperature mineral chamber samples. As a model ecosystem, the identification of pioneering consortia in deep‐sea hydrothermal vents may help advance the understanding of how early microbial life forms gained a foothold in hydrothermal systems on early Earth and potentially on other planetary bodies.

Marinobacter alkaliphilus sp. nov., a novel alkaliphilic bacterium isolated from subseafloor alkaline serpentine mud from Ocean Drilling Program Site 1200at South Chamorro Seamount, Mariana Forearc - Ken Takai; Craig L. Moyer; Masayuki Miyazaki; Yuichi Nogi; Hisako Hirayama; Kenneth H. Nealson; Koki Horikoshi (Extremophiles, 2005)

Rapid localization of transgenes in mouse chromosomes with a combined Spectral Karyotyping/FISH technique - Sei-ichi Matsui; Sheila Sait; Craig A. Jones; Norma Nowak; Kenneth W. Gross (Mammalian Genome, 2002)

The Northeast Pacific GLOBEC Program: Coastal Gulf of Alaska - Thomas Weingartner; Kenneth Coyle; Bruce Finney; Russell Hopcroft; Terry Whitledge; Richard Brodeur; Michael Dagg; Edward Farley; Dale Haidvogel; Lew Haldorson; Al Hermann; Sarah Hinckley; et al. (Oceanography, 2002)

Accurate headspace analysis of ƒCO 2 in discrete water samples using batch equilibration - Craig Neill; Kenneth M. Johnson; Ernie Lewis; Douglas W. R. Wallace (Limnology and Oceanography, 1997)
A high‐accuracy, batch‐equilibration, static‐headspace technique for the determination of the fugacity of CO 2 ( f CO 2 ) in discrete water samples is described. The technique was designed for monitoring small changes of CO 2 in the ocean and has accuracy and precision ( 2 and C T , is comparable to or better than is generally attained using potentiometric titration. Compared with C T and total alkalinity measurements, the small sample volume and rapid analysis time makes it practical to perform analysis of multiple replicates in order to improve confidence in the result. The method is readily applicable to experimental studies such as incubations as well as to time‐series measurements of in situ biological metabolism. Because the analysis employsgas chromatography, the technique can be acapted to measure simultaneously a suite of gases dissolved in seawater.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)